Enclaves of America : the Rhetoric of American Political Architecture Abroad, 1900-1965. - Robin, Ron Theodore (Princeton : Princeton University Press, 2014)
Whether determining the style of its embassies or the design of overseas cemeteries for Americans killed in battle, the U.S. government in its rise to global leadership greatly valued architectural symbols as a way of conveying its power abroad. In order to explain the political significance of American monuments on foreign soil, this illustrated book explores the efforts made by the United States from 1900 to 1965 to enhance its image as a military and economic force with displays of artistic achievement. Originally published in 1996. The Princeton Legacy Library uses th.
List of Illustrations ; Preface ; Abbreviations; Introduction; PART ONE; 1. Prologue: Hesitant Beginnings; 2. Incident at Sivry-sur -Meuse: Great War Monuments and Cemeteries in Western Europe; 3. From Palace to Plantation House: The Political Architecture of American Embassies, 1926-1932; PART TWO; 4. Interlude: MarkingTime, 1933-1945; 5. ""Our Own Land on Foreign Soil"" : The Overseas Military Cemeteries of World War II; 6. Foreign Bodies: American Imperial Architecture, 1945-1965; 7. Epilogue: Retreat; Notes; Bibliographical Essay; Index.
JSTOR
Keywords: Embassy buildings -- United States; National cemeteries, American; Architecture and state -- United States; Architecture, American; Ambassades (Édifices) -- États-Unis.; Cimetières militaires américains.; Architecture -- Politique gouvernementale -- États-Unis.; Architecture américaine.; ARCHITECTURE -- History -- General; ARCHITECTURE -- Buildings -- Public, Commercial & Industrial; Architecture, American; Architecture and state; Embassy buildings; National cemeteries, American; United States